Cyberlaw for global E-business finance, payments, and dispute resolution - Kubota, Takashi (Premier reference source, 2008)
This book examines cyberlaw discussions worldwide on topics such as cybercrime and risk management, comparative electronic trading systems of securities, digital currency regulation, jurisdiction and consumer protection in cross-border markets, and case law on international bank transfers. An invaluable resource for policy-makers, business experts, lawyers, scholars, and researchers, this book provides comprehensive research from a global perspective on the legal, technical, and financial implications of e-business